Scientific challenges for the Allin Kawsay - Mazeres-Gaitero, Francisco Javier (2024)
In the framework of the 35th Anniversary of the University of Huánuco (Peru), the DESAFÍOS Magazine, specialized in the dissemination of scientific knowledge related to the field of social sciences and humanities, decided to join the celebrations for this significant date for our higher education institution by announcing the call for the first special dossier of the Magazine in its brand new fourteen years of life.